Water redistribution in experimentally deformed natural milky quartz single crystals—Implications for H2O‐weakening processes. Issue 2 (8th February 2017) - Stünitz, H.; Thust, A.; Heilbronner, R.; Behrens, H.; Kilian, R.; Tarantola, A.; Fitz Gerald, J. D.
Abstract: Natural quartz single crystals were experimentally deformed in two orientations: (1) ⊥ to one prism plane and (2) in O + orientation at 900 and 1000°C, 1.0 and 1.5 GPa, and strain rates of ~1 × 10 −6  s −1 . In addition, hydrostatic and annealing experiments were performed. The starting material was milky quartz, which consisted of dry quartz with a large number of fluid inclusions of variable size up to several 100 µm. During pressurization fluid inclusions decrepitated producing much smaller fluid inclusions. Deformation on the sample scale is anisotropic due to dislocation glide on selected slip systems and inhomogeneous due to an inhomogeneous distribution of fluid inclusions. Dislocation glide is accompanied by minor dynamic recovery. Strongly deformed regions show a pointed broad absorption band in the ~3400 cm −1 region consisting of a superposition of bands of molecular H2 O and three discrete absorption bands (at 3367, 3400, and 3434 cm −1 ). In addition, there is a discrete absorption band at 3585 cm −1, which only occurs in deformed regions and reduces or disappears after annealing, so that this band appears to be associated with dislocations. H2 O weakening in inclusion‐bearing natural quartz crystals is assigned to the H2 O‐assisted dislocation generation and multiplication. Processes in these crystals represent recycling of H2 O between fluid inclusions, cracking and crack healing, incorporation of structurally bound H in dislocations, release of H2 O from dislocations during recovery, and dislocation generation at very small fluid inclusions. The H2 O weakening by this process is of disequilibrium nature because it depends on the amount of H2 O available. Key Points: Brittle and plastic deformation in quartz are intimately connected through crack healing processes in the presence of aqueous fluids H2 O weakening takes place by dislocation generation and multiplication at healed cracks and very small fluid inclusions H2 O is recycled between fluid inclusions and structurally bound H in dislocations and vice versa